ON THE GALACTIC DISTRIBUTIONS OF RADIO PULSARS AND PLASMA DENSITY - Ankay, A.; Yazgan, E.; Kutukcu, P. (ASTRONOMICAL OBSERVATORY BELGRADE, 2016)
A brief review of distance measurement methods for some astronomical sources is presented. Galactic plasma density distribution as related to the distribution of radio pulsars is discussed and a method for constructing relations between dispersion measure and distance for Galactic radio pulsars in small solid angle intervals is described. Dispersion measure distance relations for radio pulsars based on this approach in the Galactic longitude and latitude intervals of Delta l = 0 degrees +/- 2 degrees and Delta b = 0 degrees +/- 2 degrees are displayed and comparisons are made with the predictions of the two commonly used models.
Keywords: pulsars: general; ISM: structure; plasmas; STAR-FORMING REGIONS; PERSEUS SPIRAL ARM; X-RAY-ABSORPTION; MILKY-WAY; TRIGONOMETRIC PARALLAXES; SPATIAL-DISTRIBUTION; MILLISECOND PULSARS; OPTICAL EXTINCTION; HII-REGIONS; INTERSTELLAR-MEDIUM; Astronomy & Astrophysics